A NEW SLIP-LINE FIELD MODELING OF ORTHOGONAL MACHINING FOR A WORN TOOL - Uysal, Alper; Altan, Erhan (INT INST INFORMATICS & SYSTEMICS, 2011)
The importance of quantitatively estimating the technological performance of machining operations such as tool life, forces, power and surface finish attracts growing attention due to ever increasing applications of machining technologies in a wide variety of modern industries. This performance information is required for the selection and design of machine tools and cutting tools, as well as the optimization of cutting conditions. The machining performance is known to vary significantly with the progression of tool wear. This is because the tool wear formed at different tool faces changes the original tool geometry/configuration thus resulting in unexpected machining performance. In all types of tool wear, the flank wear has attracted maximum attention, since the amount of flank wear is often used in determining the tool life. A new slip-line model for orthogonal machining for a worn tool with flank wear and its associated hodograph are developed in this study. The entire slip-line field consists of 11 sub-regions, five slip-line angles (theta(1), theta(2), delta(2), eta and psi) and two angles of vertices (alpha(1) and alpha(2)). Mathematical formulation of the model is established based on Dewhurst and Collins's matrix technique. The new model predicts the cutting force, thrust force, ploughing force, chip up-curl radius, chip thickness and thickness of the primary shear zone.
Keywords: slip-line; worn tool; orthogonal machining; ROUNDED-EDGE TOOL; FLANK WEAR; OPERATIONS; FORCES; Computer Science